Maritime navigation and radiocommunication equipment and systems. Automatic Identification Systems (AIS). Class A shipborne equipment of the automatic identification system (AIS). Operational and performance requirements, methods of test and required test results Part 2, (13th November 2018) - British Standards Institution,
No abstract available